A chemotaxonomic investigation of cuticular hydrocarbons from selected scarab beetles (O:Col., F:Scarabaeidae) of Kubah National Park, Sarawak - Rizoh, bin Bosorang (Universiti Malaysia Sarawak (UNIMAS), 2007)
Taxonomy based on differences in morphological characters and biosystematics studies have been widely used to classify beetles. However, in this research, different approach was used by investigating the vari(tion ofhydrocarbon pattern in curculionid beetles from family Curculionidae by using cuticular hydrocarboI!.lThe cuticular lipids were extracted and evaluated from four different species of curculionid beetles which were Rhynchophorus schach, Odoiporus longicollis, Sitophilus zeamays and Sitophilus oryzae. The cuticular hydrocarbon ofcurculionid beetles were extracted using n-hexane and analyzed through Gas ChromatoraphyFID. Sixteen types of n-akanes were found on entire species and the hydrocarbon chain length were varied from C20 to C35• Odd carbon chain of n-alkanes were dominated in proportion of n-alkane in the entire species. N-tricosane, fl-hezacosane, n-heptacosane, n-octacosane, n-hentriacontane were majority carbon present in all the selected curculionid beetles.